2002
DOI: 10.1517/13543784.11.6.787
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor agonists for treating prolactinomas

Abstract: Prolactinomas are the most common hormone-secreting pituitary tumours and cause infertility and gonadal and sexual dysfunction in both sexes. The approach to prolactinomas has changed in the last 25 years thanks to the availability of dopaminergic drugs characterised by a potent prolactin-inhibitory effect, a tumour shrinking effect associated with a satisfactory tolerability. In more recent years, cabergoline 1-[(6-allelylergolin-8beta-yl)carbonyl]-1-[3-(dimethylamino) propyl]-3-ethyl-urea an ergoline derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 112 publications
3
54
0
8
Order By: Relevance
“…Unlike Cb2, quinagolide is unlikely to affect cardiac valve tissue and, therefore, is not expected to induce proliferation of fibroblasts (Roth 2007) or regurgitation. In addition, quinagolide has a much shorter half-life (w17 h) than Cb2 (w63-69 h; Colao et al 2002), thus minimizing exposure during organogenesis for women who wish to become pregnant while under treatment with DRD2-A. Inducing a hyperprolactinemic state in the event of DRD2-A proving ineffective in the treatment of women with endometriosis may be ethically questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Cb2, quinagolide is unlikely to affect cardiac valve tissue and, therefore, is not expected to induce proliferation of fibroblasts (Roth 2007) or regurgitation. In addition, quinagolide has a much shorter half-life (w17 h) than Cb2 (w63-69 h; Colao et al 2002), thus minimizing exposure during organogenesis for women who wish to become pregnant while under treatment with DRD2-A. Inducing a hyperprolactinemic state in the event of DRD2-A proving ineffective in the treatment of women with endometriosis may be ethically questionable.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a meta-analysis showed that the proportion of patients with persisting normoprolactinemia after DA withdrawal was 21% in microprolactinomas and 16% in macroprolactinomas respectively, despite nearly all consisting of female prolactinomas (6). Furthermore, there are several other major drawbacks in DA including frequent side effects, extortionate price, and long-term administration (7)(8)(9). Some other studies have reported that drug resistance in males is remarkably more frequent relative to that in female patients (24-30 vs 5-18%) (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…3 Medical therapy with dopamine receptor agonists is the initial treatment of choice. 4,5 Cabergoline is more effective than bromocriptine and is considered as firstline agent as it has higher affinity for dopamine receptor binding sites with superior drug compliance and low incidence of side effects. 6,7 In our case, Cabergoline was started initially with 0.5 mg twice weekly and it was increased step wise to 3 mg per week.…”
Section: Discussionmentioning
confidence: 99%